(1230) Compromise solutions in multi objective linear programming problems حلول التوفيق في مسائل البرمجة الخطية متعددة الأهداف - Nykowski, I.J. (The Institute Of National Planning., 2018)
This paper discusses some problems of multiple objective linear programming /MOLP/ solving and MOLP optimal solutions finding. MOLP model is formulated as in /8/. After concise MOLP historical review the problem definition and optimal solutions finding, in relation to information on objective functions, is presented in section 2.